How institutions and organizations contribute to making water accessible to farmers - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Experience in the past 30 years of irrigation has shown that technology alone is not sufficient to reduce poverty, enhance food security, and increase rural livelihoods. In many cases, farmers have not adopted or maintained the technologies, or the poor, women, and other marginalized groups have not enjoyed the benefits of technologies. In this context, institutions and organizations of collective action can help farmers acquire and adopt the technologies that best fit their needs.